FAITH-BASED LEADERSHIP IN ISLAMIC PERSPECTIVE - Prof. Hamidullah Marazi (Journal of Islamic Management Studies, 2024)
Islam, as articulated in the Quran (2:208), serves not just as a religious framework but as a comprehensive guide for all aspects of human life, including leadership. This paper explores the principles of Islamic leadership, emphasizing accountability, consultation, teamwork, and fostering a supportive work environment. Leaders in Islam are expected to embody specific qualities and virtues while maintaining a deep sense of responsibility for their actions. Drawing on Quranic teachings and scholarly interpretations, this study contextualizes Islamic leadership within contemporary organizational settings, highlighting its relevance and application in fostering cohesive and productive workplaces. By integrating spiritual values with practical leadership strategies, Islamic leadership offers a holistic approach to achieving excellence in organizational management.